Gas Production by Monoester of Saturated Fatty Acids under Electrical Fault - Abdul Rajab; Riko Novendra; Dzaki Ahmad Fertoni; Husnul Fajri (JURNAL NASIONAL TEKNIK ELEKTRO, 2022)
This paper deals with the gas production by monoester oil intended to be used as insulating oil under an electrical discharge of low energy. The monoester contains only saturated fatty acids in its hydrocarbon chain. The electrical fault was realized by implementing an AC high voltage to hemispherical shaped electrode pairs with the gap of 2.5 mm immersed in the oil sample. The voltage application was paused when the breakdown occurred in oil and re-applied repeatedly up to 50 and 75 times to allow a high concentration of gasses produced by the oil sample. The resulting gasses were extracted from the oil sample using the headspace method and then analyzed using gas chromatography (GC). Fault identification methods, like DGA status, Key Gas, Duval Triangle, and IEC Ratio, were performed to predict the fault causing the production of such gasses. The results are compared with those of the monoester of unsaturated type. It is found that the Key Gas method is applicable for both oils under electrical discharge. The Duval Triangle and the IEC Ratio methods diagnose the electrical discharge in both monoesters but overestimate them as high energy discharge.